Agronomic and silage quality traits of forage sorghum cultivars in 1995 - M.K. Siefers; J.E. Turner; G.L. Huck; S.A. Anderson; K.K. Bolsen; Matthew A. Young; Ronald V. Pope (Kansas Agricultural Experiment Station Research Reports, 1997)
Agronomic and silage quality traits were measure d for 37 forage sorghum cultivars and three grain sorghum hybrids. The 1995 growing season was characterized by above average rainfall in the spring and early summer, and a hard freeze on September 22. At the time of the freeze, 20 cultivars had reached the early-milk to early-dough stage, 12 were in the bloom stage, and the remaining eight were still in the early- to late-boot stage . The late planting date and low plant populations resulted in below-normal whole-plant D M and grain yields. Plant height s for the grain sorghums were near normal, but the forage sorghums were well below expected plant heights. The preensiled, whole-plan t DM contents of the 37 forage sorghums ranged from 23.0 to 39.9%. As expected , the silage nutritive value traits of CP, NDF, and ADF were most favorable for the three grain sorghum hybrids and least favorable for the eight forage sorghum hybrids that were still in the boot stage when the freeze occurred.
Keywords: Cattlemen' s Day; 1997; Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 783; Beef; Sorghum; Grain; Forage; Silage; Quality traits